Membumikan Spirit Toleransi Sunan Kudus Kepada Generasi Millenial Melalui Tali Akrab - Mutiara, Kholidia Efining; Said, Nur (IAIN Palangka Raya, 2019)
Intolerance, violence, riots, terror to religious leaders, hoax news, expressions of hatred, provocative issues, in the name of religion are sources of animosity between people and groups. This triggers national dimensions such as in Indonesia and even the world. Therefore this research focuses on national studies, which seeks to earthing the spirit of tolerance of teachings through the struggle of Sunan Kudus, which is implemented to the millennial generation, through interfaith communities and beliefs (Tali Akrab). This study uses phenomenological approach and content analysis by collecting data through observation, interviews and documentation from 2014 to 2018. The findings revealed that there was a the strengthening of tolerance value of Sunan Kudus era, which can be applied to Millennials through (Tali Akrab), where this activity can produce one of the efforts to strengthen religious tolerance.